Congenital cystic adenomatoid malformation: a case report - Haryo Aribowo; Divva Aurelia Azhalisita Amelinda; Ghifari Farandhi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Congenital cystic adenomatoid malformation (CCAM) is a rare condition defined by multiple cysts produced in the lung that occur during the fetal period, with respiratory distress as presenting symptoms. Untreated CCAM may lead to repeated lung infection and pneumothorax. Many surgical techniques have been used to treat CCAM. However, those techniques showed various results. Moreover, less studies were performed to evaluate the effect of those surgical techniques in treating CCAM patients. We reported a management of  a rare pediatric case of CCAM referred to the Department of Thoracic and Cardiovascular Surgery, Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada/Dr. Sardjito General Hospital. The patient was a 29-day-old male baby who presented with pneumothorax on the right lung due to CCAM. The plan of treatment for the patient was lobectomy until pneumonectomy on the affected lung. During the thoracotomy procedure, we found that all lobes in the right lung were covered with fibrous tissue. Based on this finding, a decortication procedure to remove the fibrous tissue continued by a bullectomy procedure with the insertion of a chest tube were performed. The patient continuously showed improvement in breathing and wound healing, thus making the patient discharged from the hospital on the nineteenth postoperative day. The cause of CCAM is thought to be congenital abnormalities of the bronchiole epithelium that produce multiple cysts. Due to its rarity and lack of research on CCAM, many CCAM patients are misdiagnosed/underdiagnosed. Common surgical methods used in this patient are lobectomy with continuation until pneumonectomy or bilobectomy, if necessary, to prevent recurrence. Parenchymal saving methods can be considered because they have the same outcome as lobectomy. As performed in this patient, thoracotomy decortication continued with bullectomy is adequately capable of alleviating respiratory distress symptoms and is thus described as successful.